PENGARUH CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR), DAN NON PERFORMING LOAN (NPL) KREDIT UMKM TERHADAP JUMLAH KREDIT UMKM DI INDONESIA - Gatri Pilar Mandiri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The present research examined the optimum bank lending system to SMEs. The previous research indicated that the lending system was not optimum, the SMEs loan portofolio target was still below 20%. Therefore, this present study attempt to examines the factors that may affect SMEs lending systems such as Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Non- Performing Loans (NPLs) credit of SMEs by Stated Bank, National Private Bank, and Rural Bank. Time period of research was from 2012 to July 2016 and using panel data regression analysis. The results of the panel data regression suggested that CAR, LDR, and NPL’s credit of SME have significant effect on SME credits. This is due to the increase of total funds collected by the State Banks, National Private Banks, and Rural Banks, so that those banks still able to lend SME’s credit. In this case, the banks have to maintain the LDR and NPL to prevent exceeding the limit regulated by the government.Keywords: credit SMEs, Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Non Performing Loan (NPL) credit of SME